Establishing a Core Outcome Set for Autosomal Dominant Polycystic Kidney Disease: Report of the Standardized Outcomes in Nephrology-Polycystic Kidney Disease (SONG-PKD) Consensus Workshop. - Cho, Yeoungjee; Tong, Allison; Craig, Jonathan C.; Mustafa, Reem A.; Chapman, Arlene; Perrone, Ronald D.; Ahn, Curie; Fowler, Kevin; Torres, Vicente; Gansevoort, Ron T.; Ong, Albert C. M.; Coolican, Helen; et al. (American Journal of Kidney Diseases, 2021)
The omission of outcomes that are of relevance to patients, clinicians, and regulators across trials in autosomal dominant polycystic kidney disease (ADPKD) limits shared decision making. The Standardized Outcomes in Nephrology-Polycystic Kidney Disease (SONG-PKD) Initiative convened an international consensus workshop on October 25, 2018, to discuss the identification and implementation of a potential core outcome set for all ADPKD trials. This article summarizes the discussion from the workshops and the SONG-PKD core outcome set. Key stakeholders including 11 patients/caregivers and 47 health professionals (nephrologists, policy makers, industry, and researchers) attended the workshop. Four themes emerged: "Relevance of trajectory and impact of kidney function" included concerns about a patient's prognosis and uncertainty of when they may need to commence kidney replacement therapy and the lack of an early prognostic marker to inform long-term decisions; "Discerning and defining pain specific to ADPKD" highlighted the challenges in determining the origin of pain, adapting to the chronicity and repeated episodes of pain, the need to place emphasis on pain management, and to have a validated measure for pain; "Highlighting ADPKD consequences" encompassed cyst-related complications and reflected patient's knowledge because of family history and the hereditary nature of ADPKD; and "Risk for life-threatening but rare consequences" such as cerebral aneurysm meant considering both frequency and severity of the outcome. Kidney function, mortality, cardiovascular disease, and pain were established as the core outcomes for ADPKD.
EVALuna2:418901